Analisis Transformasi Ekonomi Sektor Pertanian Antar Provinsi Di Pulau Kalimantan - Amak Priyatna; Dewi Rahayu; Saipudin Saipudin (CV. Syntax Corporation Indonesia, 2022)
The direction of transformation decreases the dependence of natural resources by shifting towards industry and services so that it is necessary to know the pattern of transformation related to changes in the growth rate of contribution and competitiveness. The agricultural sector in 2020 contributed 50-25% in the formation of PDRB spread across 44 districts from 51 districts on the island of Kalimantan. Secondary data of Provincial PDRB on Kalimantan Island 2010-2020 as a reference for research. Location Quotien and Shift-Share analysis was used in this study and the results were measurable considerations of regional development planning. The results showed the agricultural sector maintained a positive contribution and the subsectors had competitiveness namely Plantation, Horticulture, Fisheries and Livestock. There has been a transformation of agriculture marked by the contribution of fluctuations and decreases in the rate of growth in the future need to be anticipated. Accelerated transformation through the policy of downstreaming agricultural commodities but hampered by the regeneration of competent human resources and the slow application of integrated agricultural technology